A Seedbed for Innovation? Eight European Commission work plans and their impact on the commercialisation of the information marketplace - Worlock, David (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2017)
This paper offers a personal view of the nature, role and impact of European Research Programmes on the publishing industry.